Milk protein complexation enhances post prandial vitamin D3 absorption in rats. Issue 6 (5th June 2020) - Lindahl, Ida Emilie I.; Danielsen, Marianne; Dalsgaard, Trine K.; Rejnmark, Lars; Bollen, Peter; Bertram, Hanne Christine
Abstract : This study investigated the effect of complexation with whey and casein protein, respectively, on post prandial absorption of vitamin D3 . Abstract : This study investigated the effect of complexation with whey and casein protein, respectively, on post prandial absorption of vitamin D3 . For this purpose, Sprague-Dawley rats ( n = 78) were administered 840 IU vitamin D3 dissolved in ethanol and either (i) complexed with whey protein isolate (protein : vitamin ration 2 : 1), (ii) complexed with caseinate (protein : vitamin ration 2 : 1), or (iii) provided in a water solution. Serum concentrations of vitamin D3, 25-hydroxyvitamin D3 and 24, 25-dihydroxyvitamin D3 were measured before and 2, 3, 4, 5, 6, 7, 8, and 10 hours after administration of vitamin D3 . Significant effects of complexation on serum concentrations of vitamin D3, 25-hydroxyvitamin D3 and 24, 25-dihydroxyvitamin D3 were demonstrated. Complexation with whey protein isolate resulted in the fastest and highest absorption of vitamin D3 while an effect of complexation with caseinate was evident but more modest and non-significant. In conclusion, the study demonstrates that complexation with milk proteins is an efficient strategy to enhance bioaccessibility of vitamin D3 .